Pediatric echocardiograms performed at primary centers: Diagnostic errors and missing links! - Rahul P Saraf; P V Suresh; Sunita Maheshwari; Sejal S Shah (Wolters Kluwer Medknow Publications, 2015)
Aim: The present study was undertaken to assess the accuracy of pediatric echocardiograms done at non-tertiary centers and to evaluate the relationship of inaccurate interpretations with age, echocardiogram performer and complexity of congenital heart disease (CHD). Materials and Methods: The echocardiogram reports of 182 consecutive children with CHD (5 days-16 years) who were evaluated at a non-tertiary center and subsequently referred to our center were reviewed. Age of the child at echocardiogram, echocardiogram performer and complexity of CHD were noted. These reports were compared with echocardiogram done at our center. Discrepancies were noted and categorized. To assess our own error rate, we compared our echocardiogram reports with the findings obtained during surgery (n = 172), CT scan (n = 9) or cardiac catheterization reports (n = 1). Results: Most of the children at the non-tertiary center (92%) underwent echocardiogram by personnel other than a pediatric cardiologist. Overall, diagnostic errors were found in 69/182 (38%) children. Moderate and major discrepancies affecting the final management were found in 42/182 (23%) children. Discrepancies were higher when the echocardiogram was done by personnel other than pediatric cardiologist (P < 0.01) and with moderate and high complexity lesions (P = 0.0001). There was no significant difference in proportion of these discrepancies in children ≤ 1 year vs. >1 year of age. Conclusions: A significant number of pediatric echocardiograms done at non-tertiary centers had discrepancies that affected the management of these children. More discrepancies were seen when the echocardiogram performer was not a pediatric cardiologist and with complex CHD.